The immunosuppressive effects and mechanisms of loureirin B on collagen-induced arthritis in rats - Zou, Yan; Zhao, Qianru; Zhang, Xu; Yu, Hui; Zhou, Yongsheng; Li, Ziyi; Xiao, Min; Xiang, Qiu; Zhang, Lirong; Shi, Wenyi; Tao, Haobo; Chen, Lvyi; et al. (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is a common disease mainly affecting joints of the hands and wrists. The discovery of autoantibodies in the serum of patients revealed that RA belonged to the autoimmune diseases and laid a theoretical basis for its immunosuppressive therapy. The pathogenesis of autoimmune diseases mainly involves abnormal activation and proliferation of effector memory T cells, which is closely related to the elevated expression of Kv1.3, a voltage-gated potassium (Kv) channel on the effector memory T cell membrane. Drugs blocking the Kv1.3 channel showed a strong protective effect in RA model animals, suggesting that Kv1.3 is a target for the discovery of specific RA immunosuppressive drugs. Our previous studies showed that Loureirin B (LrB) could block Kv1.3 channels and calcium ion elevation in an activated T cell line. In the present study, we synthesized LrB and studied the effects of LrB on collagen-induced arthritis (CIA) in rats. We observed that LrB effectively reduced the clinical score and relieved joint swelling. The results of flow cytometry indicated that LrB could decrease the percentage of CD4+ T cells, while increase the percentage of CD8+ T cells in peripheral blood mononuclear and spleen of rats with CIA. An enzyme-linked immunosorbent assay showed that the concentrations of inflammatory cytokines interleukin (IL)-1β, IL-2, IL-6, IL-10 and IL-17 in the serum of CIA rats were significantly reduced by LrB. The results of RT-PCR showed that Kv1.3 mRNA in the peripheral blood mononuclear cells of CIA rats was significantly higher than that of the control and significantly decreased in the LrB treatment groups. In addition, we confirmed in cell models that LrB significantly decreased Kv1.3 protein on the cell membrane and inhibited the activation of Nuclear Factor of Activated T Cells 1 (NFAT1) with immune stimulus. In summary, this study revealed that LrB could block NFAT1 activation and reduce Kv1.3 expression in activated T cells, thus inhibiting the proliferation of lymphocytes and the release of inflammatory cytokines, thereby effectively weakening the autoimmune responses in CIA rats. The effects of immunosuppression due to LrB revealed its potential medicinal value in the treatment of RA.